Safety of 80 antidepressants, antipsychotics, anti‐attention‐deficit/hyperactivity medications and mood stabilizers in children and adolescents with psychiatric disorders: a large scale systematic meta‐review of 78 adverse effects. Issue 2 (11th May 2020) - Solmi, Marco; Fornaro, Michele; Ostinelli, Edoardo G.; Zangani, Caroline; Croatto, Giovanni; Monaco, Francesco; Krinitski, Damir; Fusar‐Poli, Paolo; Correll, Christoph U.
Abstract : Mental disorders frequently begin in childhood or adolescence. Psychotropic medications have various indications for the treatment of mental disorders in this age group and are used not infrequently off‐label. However, the adverse effects of these medications require special attention during developmentally sensitive periods of life. For this meta‐review, we systematically searched network meta‐analyses and meta‐analyses of randomized controlled trials (RCTs), individual RCTs, and cohort studies reporting on 78 a priori selected adverse events across 19 categories of 80 psychotropic medications – including antidepressants, antipsychotics, anti‐attention‐deficit/hyperactivity disorder (ADHD) medications and mood stabilizers – in children and adolescents with mental disorders. We included data from nine network meta‐analyses, 39 meta‐analyses, 90 individual RCTs, and eight cohort studies, including 337, 686 children and adolescents. Data on ≥20% of the 78 adverse events were available for six antidepressants (sertraline, escitalopram, paroxetine, fluoxetine, venlafaxine and vilazodone), eight antipsychotics (risperidone, quetiapine, aripiprazole, lurasidone, paliperidone, ziprasidone, olanzapine and asenapine), three anti‐ADHD medications (methylphenidate, atomoxetine and guanfacine), and two mood stabilizers (valproate and lithium). Among these medications with data on ≥20% of the 78 adverse events, a safer profile emerged for escitalopram and fluoxetine among antidepressants, lurasidone for antipsychotics, methylphenidate among anti‐ADHD medications, and lithium among mood stabilizers. The available literature raised most concerns about the safety of venlafaxine, olanzapine, atomoxetine, guanfacine and valproate. Nausea/vomiting and discontinuation due to adverse event were most frequently associated with antidepressants; sedation, extrapyramidal side effects, and weight gain with antipsychotics; anorexia and insomnia with anti‐ADHD medications; sedation and weight gain with mood stabilizers. The results of this comprehensive and updated quantitative systematic meta‐review of top‐tier evidence regarding the safety of antidepressants, antipsychotics, anti‐ADHD medications and mood stabilizers in children and adolescents can inform clinical practice, research and treatment guidelines.